Context Input Process Product Evaluation of IMTAQ Program Development for Class VII Students of SMPN 23 Palembang - Etika Vestia; Muhamad Yahya; Febriyanti Febriyanti; Tamsik Udin; Miftahus Surur (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
This study aims to determine the extent to which the implementation objectives of the IMTAQ program development have been carried out to determine whether the program was discontinued, whether it was carried out later, and whether revisions/improvements were needed. This is descriptive qualitative research with data collection techniques using observation, interviews, and documentation. The data that has been collected is then analyzed descriptively and qualitatively. The results of the study indicate that the implementation of the IMTAQ program at SMPN 23 Palembang has created a conducive atmosphere and a religious culture. Integrating the IMTAQ program into learning is related to the faith and piety of students. In the IMTAQ program, activities to read the Qur'an are not spared. Furthermore, the school carries out the IMTAQ program development for students by providing examples, wise advice, habituation, rewards and punishments. The supporting factors are 1) motivation and support from the school community; 2) motivation and support from parents of students; 3) understanding of parents and society about religious teachings. While the inhibiting factors are 1) facilities and infrastructure, 2) funds, 3) supervisors, 4) and limited sources.